Significant UK Environmental Law Cases 2021–22. (28th June 2022) - Helme, Ned; Boukraa, Adam; David, Stephanie; Leydon, Eleanor
Abstract: This article comments on significant UK environmental law cases for the period 1 April 2021 to 31 March 2022. It begins with an overarching introduction focussing on the standard of review in environmental claims in the public law context and drawing attention to tension on the domestic bench on matters of approach. It then addresses a selection of significant cases in the fields of climate change (both inside and outside the environmental impact assessment regime), strategic environmental assessment, habitats, species, discretion under section 31(2A) of the Senior Courts Act 1981, representative actions under CPR Rule 19.6, waste, licensing and human rights.